2021
DOI: 10.3390/ijms22052774
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Pharmacological In Vitro Investigations of Novel Shikonin Derivatives with a Special Focus on Cyclopropane Bearing Derivatives

Abstract: Melanoma is the deadliest form of skin cancer and accounts for about three quarters of all skin cancer deaths. Especially at an advanced stage, its treatment is challenging, and survival rates are very low. In previous studies, we showed that the constituents of the roots of Onosma paniculata as well as a synthetic derivative of the most active constituent showed promising results in metastatic melanoma cell lines. In the current study, we address the question whether we can generate further derivatives with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 65 publications
(98 reference statements)
0
11
0
Order By: Relevance
“…Shikonin and acetylshikonin are naturally occurring shikonin derivatives [ 15 , 16 , 17 ]. Cyclopropylshikonin was synthesized in a previous study and found to be the most cytotoxic compound out of a screening of novel shikonin derivatives [ 18 ]. It could be previously shown that the naphthoquinone scaffold, including the hydroxyl groups, is important for the activity of shikonin derivatives.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Shikonin and acetylshikonin are naturally occurring shikonin derivatives [ 15 , 16 , 17 ]. Cyclopropylshikonin was synthesized in a previous study and found to be the most cytotoxic compound out of a screening of novel shikonin derivatives [ 18 ]. It could be previously shown that the naphthoquinone scaffold, including the hydroxyl groups, is important for the activity of shikonin derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…It could be previously shown that the naphthoquinone scaffold, including the hydroxyl groups, is important for the activity of shikonin derivatives. Moreover, the side chain was reported to further influence the overall activity [ 18 ]. Both HC and pCH-OA showed a dose-dependent inhibition of cell viability after treatment with shikonin derivatives ( Figure 1 B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, among other derivatives, we developed a novel shikonin derivative—cyclopropylacetylshikonin—which was more effective against two metastatic melanoma cell lines than DMAS [ 14 ]. A similar derivative bearing another cyclopropane moiety was also shown by our group to exhibit promising effects in melanoma cell lines [ 15 ]. In the current study, we report on the synthesis and pharmacological effects of another novel shikonin derivative (SK119), which is active in a nano-molar range and exhibited several promising in vitro effects.…”
Section: Introductionmentioning
confidence: 99%